Facies analysis and petrography of the upper Cretaceous deposits in the northen Neuquen basin: implications for the beginning of the Foreland stage (Latin American Journal of Sedimentology and Basin Analysis, 2020)
The Neuquén Basin is one of the main hydrocarbon-generating basins in Argentina. This, along with a large sedimentary record, has made it the subject of numerous geological studies. Most of these studies focus on the central part of the basin, with very little background in the area of the high mountain ranges in Mendoza (Fig. 1). The rocks studied belong to the Bajada del Agrio Group, which includes the Huitrín and Rayoso formations, and the Diamante Formation equivalent to the Neuquén Group (Fig. 2 and 3). These units correspond to the transition between the back-arc and foreland stages (Lower Cretaceous-Upper Cretaceous).The goal of this work is to perform a detailed sedimentological, petrographic and stratigraphic study analyzing facies, stratigraphic relationships and provenance, with the aim of adjusting the depositional model of the succession representing the Lower Cretaceous-Upper Cretaceous transition.A sedimentological section was measured at Vega de los Patos (Fig. 4), approximately 100 km north of Malargüe. In that section fifteen facies were identified (Table 1), five facies associations (Fig. 5, 6, 7, 8 and 9) and two depositional cycles. The sedimentological analysis of the succession exposed at Vega de los Patos suggests that the analyzed section represents a transition between deposits in a marginal marine environment and fluvial fans (Fig. 15). This model allows relating the vertical variations of the facies with the progressive migration of the system, which could be related to tectonic uplift pulses. For the petrographic analysis included eight samples of medium sandstones, two of pelites, two of gypsum/anhydrite and one carbonate. The sandstones were classified as feldspathic lithoarenites and lithoarenites (Fig. 12). The petrographic analysis also showed that the sedimentary source of the analyzed sequence is mixed, between dissected arc and recycled orogen (Fig. 12).However, it is important to highlight the appearance of conglomerate levels with carbonate lithic fragments (Fig. 13) of the Agrio Formation (Lower Cretaceous) recognized in other sectors of the basin. This suggests a contribution of part of the lower Mesozoic carbonate sequence, probably as the result of a tectonic uplift pulse. Finally, the sandstones are affected by the precipitation of carbonate, zeolitic and to a lesser extent ferruginous cement (Fig. 10) and the carbonate rocks show an intense dolomitization and evidence of microfossils (Fig. 11).The analysis by X-ray diffractometry served to determine that the zeolitic cement observed petrographically was analcime (Fig. 14). It also revealed variations in the composition of clays along the section (Fig. 16). Such variations indicate arid and alkaline deposition conditions for the base of the Diamante Formation that change to a humid climate environment and acidic conditions in the middle sector.In the center of the basin, the transition between the bac-arc and foreland stages is related to the Intercenonian unconformity. However, there are no previous works that mention it in the study area. In previous works, an erosion or no deposit gap of 25 Ma was established, which include the entire Rayoso Formation, with the Huitrín Formation in contact with the Neuquén Group. Using a maximum age of deposition of the Huitrín Formation 100 km south of the study area (124 Ma) and those made in the first sandstone of the Diamante Formation in the study area (107 Ma) the gap would go down to 17Ma. Considering that there was no evidence of unconformity along the studied section, a transition or a paraconformity between the strata analyzed is assumed.
Keywords: Neuquén Basin; fluvial fan; Diamante Formation; Bajada del Agrio Group; Upper Cretaceous